Whole-exome sequencing in 415,422 individuals identifies rare variants associated with mitochondrial DNA copy number - Pillalamarri, Vamsee; Shi, Wen; Say, Conrad; Yang, Stephanie; Lane, John; Guallar, Eliseo; Pankratz, Nathan; Arking, Dan E. (HGG advances, 2023)
Inter-individual variation in the number of copies of the mitochondrial genome, called mitochondrial DNA copy number (mtDNA-CN), reflects mitochondrial function and has been associated with various aging-related diseases. We examined 415,422 exomes of self-reported White ancestry individuals from the UK Biobank and tested the impact of rare variants, at the level of single variants and through aggregate variant-set tests, on mtDNA-CN. A survey across nine variant sets tested enrichment of putatively causal variants and identified 14 genes at experiment-wide significance and three genes at marginal significance. These included associations at known mtDNA depletion syndrome genes (mtDNA helicase TWNK, p = 1.1 × 10−30; mitochondrial transcription factor TFAM, p = 4.3 × 10−15; mtDNA maintenance exonuclease MGME1, p = 2.0 × 10−6) and the V617F dominant gain-of-function mutation in the tyrosine kinase JAK2 (p = 2.7 × 10−17), associated with myeloproliferative disease. Novel genes included the ATP-dependent protease CLPX (p = 8.4 × 10−9), involved in mitochondrial proteome quality, and the mitochondrial adenylate kinase AK2 (p = 4.7 × 10−8), involved in hematopoiesis. The most significant association was a missense variant in SAMHD1 (p = 4.2 × 10−28), found on a rare, 1.2-Mb shared ancestral haplotype on chromosome 20. SAMHD1 encodes a cytoplasmic host restriction factor involved in viral defense response and the mitochondrial nucleotide salvage pathway, and is associated with Aicardi-Goutières syndrome 5, a childhood encephalopathy and chronic inflammatory response disorder. Rare variants were enriched in Mendelian mtDNA depletion syndrome loci, and these variants implicated core processes in mtDNA replication, nucleoid structure formation, and maintenance. These data indicate that strong-effect mutations from the nuclear genome contribute to the genetic architecture of mtDNA-CN. Mitochondrial DNA copy number (mtDNA-CN) is an important biomarker of aging. We tested rare nuclear genetic variants in 415,422 individuals from the UK Biobank for association with mtDNA-CN. Rare variants reveal fundamental processes related to mitochondrial biology and disease.